FUNCTIONAL MITRAL REGURGITATION: IF THE MYOCARDIUM IS GUILTY DO WE ALSO NEED TO 'REHABILITATE' THE VALVE?. Issue 1 (2015) - Pepe, Martino; Paradies, Valeria; Resta, Fabrizio; Cafaro, Alessandro; Bartolomucci, Francesco; Masi, Filippo; Quagliara, Donato; Favale, Stefano
No abstract available